Predictive value of NLRC3 levels for pulmonary hypertension in patients with chronic obstructive pulmonary disease - Yılmaz, Meltem; Mutlu, Levent Cem; Alpsoy, Şeref; Akyüz, Aydın; Çelikkol, Aliye; Kaymaz, Özlem (The European Research Journal, 2024)
Objectives: Chronic obstructive pulmonary disease (COPD) is a medical condition defined by persistent airflow limitation and respiratory symptoms caused by airway and/or alveolar abnormalities. Pulmonary hypertension (PH) is one of the cardiovascular comorbidities associated with COPD. We investigated the correlation of NLRC3 levels in patients with COPD with prognostic and surrogate parameters of PH on echocardiography and examined whether it could be used to predict PH in this patient population. Methods: A total of 80 patients diagnosed with COPD and 40 healthy volunteers as the control group were included in the study. The COPD group was further divided into two subgroups according to the systolic pulmonary artery pressure (sPAP) as follows: sPAP<35 mmHg and sPAP≥35 mmHg. The enzyme-linked immunosorbent assay (ELISA) method was used to determine the levels of NLRC3 in peripheral blood. Results: Patients with sPAP≥35 mmHg had a lower mean NLRC3 level than those with sPAP<35 mmHg (P=0.006). The NLRC3 levels showed a significant negative correlation with sPAP, tricuspid regurgitation velocity, right atrium, and pulmonary artery diameter. For NLRC3, the cut-off value was found to be 271,486 ng/L, with a sensitivity of 74%, and specificity of 63% in distinguishing patients with sPAP≥35 mmHg from all patients with sPAP<35 mmHg. Conclusions: Our study results suggest that NLRC3 levels measured from peripheral blood are predictive of PH in patients with COPD. Although the exact function of NLRC3 in the lungs, COPD, and PH have not been completely understood, we believe these findings will serve as a model for future studies.